New design space regainers: 'Lingual arch crossbow' and 'Double banded space regainer' - P Chalakka; A M Thomas; F Akkara; R Pavaskar (Wolters Kluwer Medknow Publications, 2012)
This article highlights the use of two new design space regainers - the "lingual arch crossbow" and the "double-banded space regainer." The former may be used for distalizing a mesially migrated mandibular first premolar, if it erupts prior to the canine. The latter may be used in conventional cases of interdental space loss. They both contain assemblies that function through the action of NiTi open coil springs.